1992
DOI: 10.1113/expphysiol.1992.sp003660
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a possible role of 5‐hydroxytryptamine in the genesis of fatigue in man: administration of paroxetine, a 5‐HT re‐uptake inhibitor, reduces the capacity to perform prolonged exercise

Abstract: SUMMARYSeven healthy subjects exercised to exhaustion on a bicycle ergometer at a power output corresponding to 70 % of maximum oxygen uptake after administration of either a placebo or 20 mg of paroxetine, a serotonin re-uptake inhibitor. Exercise time after paroxetine (median 94 min; range 84-127 min) was less (P < 0.05) than after placebo (median 116 min; range 86-133 min). The metabolic and cardiorespiratory responses to exercise were the same in both trials. This result supports the suggestion that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(123 citation statements)
references
References 6 publications
7
111
2
3
Order By: Relevance
“…Our results are also consistent with pharmacological studies performed in humans. It was demonstrated that oral intake of the 5-HT 1A receptor agonist buspirone or the selective serotonin reuptake inhibitor paroxetine trigger faster exhaustion during motor tasks (14,15). Moreover, during central fatigue, the gain of MNs is reduced (5, 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also consistent with pharmacological studies performed in humans. It was demonstrated that oral intake of the 5-HT 1A receptor agonist buspirone or the selective serotonin reuptake inhibitor paroxetine trigger faster exhaustion during motor tasks (14,15). Moreover, during central fatigue, the gain of MNs is reduced (5, 8).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence suggests that central fatigue correlates with increased levels of serotonin (5-HT) in the CNS. Human subjects that perform an intense motor task are faster exhausted after intake of a 5-HT 1A receptor agonist (14) or a selective serotonin reuptake inhibitor (15). In animals, injection of the 5-HT precursor tryptophan in the blood or directly in the CNS accelerates the exhaustion occurring during motor activity (16,17).…”
mentioning
confidence: 99%
“…While there is some experimental support for the hypothesis of Newsholme & Castell (2000), the evidence of a beneficial effect on exercise performance is limited. Nonetheless, the fact that pharmacological manipulation of 5-hydroxytryptamine activity can alter exercise performance (Wilson & Maughan, 1992) does suggest that nutritional interventions to produce the same effect may also be possible.…”
Section: Central Nervous System Effectsmentioning
confidence: 99%
“…Human and rat studies exploring for effects of drugs that increase 5HT synaptic transmission in brain have reported that elevating 5HT transmission reduces physical erformance (Wilson and Maughan 1992;Bailey et al 1992Bailey et al , 1993Struder et al 1998). Conversely, drugs that increase catecholamine transmission enhance physical performance (Roelands et al 2008a, b).…”
mentioning
confidence: 99%